Environmental solutions [environmental problems and the all-inclusive global, scientific, political, legal, economic, medical, and engineering bases to solve them] - Agardy, Franklin J.; Nemerow, Nelson Leonard
In our changing world, society demands more comprehensive and thoughtful solutions from environmental engineers, environmental consultants and scientists dealing with the degradation of our environment. Lead by Nelson Nemerow and Franklin Agardy, experts in business, academia, government and practice have been brought together in this book to provide guidance for these environmental professionals. The reader is presented with a variety of solutions to common and not so common environmental problems which lay the groundwork for environmental advocates to decide which solutions will work best for their particular circumstances. This book discusses chemical, biological, physical, forensic, medical, international, economic, political, industrial-collaborative solutions and solutions for rural and developing countries giving readers the freedom to evaluate a variety of options and make informed decisions. End of chapter questions and additional resources are included making this an invaluable teaching tool and ideal reference for those currently involved in improving and preserving our environment. * Contributions by international experts in government, industry, and academia. * Editors are recognized as the editors of Environmental Engineering, the best selling title published by John Wiley * The first action-oriented book for environmental engineers.